외래식물 들개미자리 (Spergula arvensis) 추출물의 식물, 토양 미생물 및 포유류에 대한 독성 - 엄헌섭(Heonseop Eom); 오상은(Sang Eun Oh); 김소연(So-Yeon Kim); 박세진(Se Jin Park); 홍민지(Minji Hong); 김성문(Songmun Kim); 황기환(Ki-Hwan Hwang); 이용호(Yong Ho Lee); 홍선희(Sun Hee Hong) (Weed & turfgrass science, 2019)
들개미자리는 중요한 침입외래잡초로써 제주도 농경지를 중심으로 빠르게 확산 및 우점하고 있다. 본 연구의 목적은 식물, 토양, 미생물 및 포유류에 대한 들개미자리의 독성 및 환경에 미치는 영향을 이해하고자 하였다. 나팔꽃에 대한 들개미자리 메탄올 추출물의 GR50 값은 6,370 mg L-1 로서 매우 낮은 활성을 나타냈다. 또한 추출물은 토양 및 경엽처리에서도 어떠한 약해를 나타내지 않았다. 무기 및 유기오염 물질과 비교할 때 황산화박테리아(377.6 mg L-1)와 조류(446.3 mg L-1)의 EC50 값이 더 높은 것으로 나타났으며, 따라서 들개미자리의 추출물은 이들에게 큰 저해효과를 일으키는 물질이라 보기 어렵다. 세포독성 시험결과, 마우스 대식세포 및 인간 각질형성세포에서의 CC50는 각각 591.4 및563.3 μg mL-1였으며, 이는 들개미자리 추출물이 낮은 수준의 세포 독성 효과를 가짐을 나타낸다. 쥐를 이용한 단회경구투여 시 2000 mg kg-1까지의 들개미자리 추출물은 사망률, 임상 증상, 부검 결과, 체중 변화 및 혈액 학적 변화를 보이지 않았다. 종합적으로, 제주도 농경지의 우점 침입외래잡초인 들개미자리는 작물, 토양, 인간 등에 미치는 독성관련 영향이 비교적 낮음을 시사한다. Corn Spurrey (Spergula arvensis) is considered as one of the most important invasive alien weeds, rapidly spreading to agricultural lands in Jeju Island. The purpose of the current study was to understand the toxicological eff ects of S. arvensis on plants, soil microorganisms, and mammals. In the plant toxicity tests, the GR50 value of morning glory for the S. arvensis extract was found to be 6,370 mg L-1, suggesting that the extract was non-toxic on plants. Moreover, the soil and foliar applications of the extract also showed that the extract rarely made adverse effects on plants. As a result of microbial toxicity tests, the EC50 values of sulfur-oxidizing bacteria (SOB) and Chlorella vulgaris for the S. arvensis extract were substantially high and accounted for 377.6 and 446.3 mg L-1, respectively. These results indicate that inhibitory eff ects of the S. arvensis extract on activity of soil microorganisms were insignifi cant. In the cytotoxicity tests, the CC50 values of RAW264.7 macrophages and human keratinocytes for the S. arvensis extract were 591.4 and 563.3 μg mL-1, respectively, demonstrating that the extract had a low level of cytotoxic eff ects. The acute toxicity test with rats revealed that single oral administration of the S. arvensis extract up to 2000 mg kg-1 did not show any mortality, clinical symptoms, necropsy findings, decreases in body weight, and hematological changes. The overall fi ndings of the present study suggest that the dominance of the invasive alien weed S. arvensis in Jeju Island can rarely cause adverse eff ects on the environment and humans. KCI Citation Count: 0